METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN MENGGUNAKAN TEKNIK HIPNOTIS - Abdul Wahab Syakhrani (Cross-border, 2018)
Learning is the spirit of an educational process, so the learning process becomes a vital part. To create an effective learning process, a teacher is required to produce innovative and creative products. Hypnoteaching is an alternative method that teachers can use in building an effective and fun learning atmosphere. This method is part of the application of hypnosis that can bring students to an atmosphere of relaxation in receiving the subject matter.